Analisis Keandalan Sistem Proteksi Kebakaran Pada Bangunan Ayola First Point Hotel Pekanbaru - Wulandari, Bheti; Trikomara, Rian (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
This study is intended to determine the value systems of fire and building safety reliability of Ayola First Point Building of Hotel Pekanbaru in case of fire. Questionnaire of this study was done twice. Analytical Hierarchy Process (AHP) was used for the first questionnaire in order to find out the weighting of fire variable which covers the completeness of its siting, rescuing utilities, passive protection system and active protection system. The second questionnaire used check-list method based on Minister Rules for General Work Number 26 Year 2008 in order to obtain the buildingâ€™s reliability value in case of fire. The results for the said value for Ayola First Point of Hotel Pekanbaru using AHP and check-list method are, respectively, 91,93% and 91,45%. Therefore, it is concluded that the buildingâ€™s safety system in case of fire is in â€œGoodâ€ condition.Keywords: Fire, Reliability, AHP